EFEKTIVITAS E-MODUL AJAR BERBASIS PEMECAHAN MASALAH UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA PADA MATA KULIAH TEORI BILANGAN - Rofiroh, Rofiroh; Nirmalasari, Dinar (Cakrawala Pedagogik, 2025)
In the era of digitalization, the world of education is innovating in developing learning methods in the classroom. One of the innovations is creating digital-based learning media such as e-teaching modules. It is hoped that this e-module can help and facilitate students in solving problems, especially in number theory courses. The aim of this research is to determine students' abilities in number theory courses. The research used was quantitative research with the research object being 37 first semester students of class E majoring in mathematics education, FKIP, Sultan Ageng Tirtayasa University. The test results using the Wilcoxon non-parametric test obtained Asymp.Sig.0.000<0.05. This means that there is a significant difference between the pre-test before using the problem solving based teaching e-module and the post-test after using the problem solving based teaching e-module.